Rumen microbial protein and milk production on different source of oilseed meals in mixed diet - MOHANAVEL, S; SRINIVAS, B (The Indian Journal of Animal Sciences, 2016)
Effects of different oilseed meals (OSM) in concentrate supplement (CS) on rumen microbial protein (MBP) and milk composition were evaluated. Deoni cows (20) were distributed to 5 equal groups. CS consisted 90% of maize grain alone (control; CG) or 30% maize grain and 60% of any one type of OSM viz., groundnut (GNM; T1), cottonseed (CSM; T2), copra (CM; T3) or mustard (MSM; T4). The rest of CS was urea, mineral mixture and common salt. Roughage fed was hybrid napier and ragi straw. DM intake (DMI) was lesser in T4 than CG. Feed efficiency was comparable between CG and TGs. Digestible and metabolizable energy were higher in T1, T2 and T3 than CG or T4. MBP in T1 (224 g/d) was 11 and 13% higher than T2 and T4, respectively. MBP in CG was comparable to T2 and T4. MBP efficiency was higher in T1 and least in T3 (40 vs. 26 g/kg DOMI). Fat corrected milk (FCM) yield was comparable between CG and TGs. Milk composition in TGs improved from third week. TS was 348, 457, 441, 358 and 339 g/d, respectively, and SNF was 237, 303, 312, 243 and 238 g/d, respectively in CG, T1, T2, T3 and T4. The study concluded that MBP was higher with GNM followed by CSM and MSM but poor with CM. GNM and CSM improved SNF and TS in milk while CM and MSM improved milk fat.